2020
DOI: 10.3390/ijms21134597
|View full text |Cite
|
Sign up to set email alerts
|

Trace Element Bioaccumulation in Stone Curlew (Burhinus oedicnemus, Linnaeus, 1758): A Case Study from Sicily (Italy)

Abstract: The study aimed to highlight the degree of trace element contamination along three sites of Sicily: the Magnisi peninsula (MP), located in proximity to the Augusta–Priolo–Melilli petrochemical plant; the Ragusa agro-ecosystem (RA), characterized by a rural landscape; and the Gela plain (GP), characterized by intensive agriculture and a disused petrochemical plant. We collected biological samples (abraded back feathers and blood) of the Stone Curlew (Burhinus oedicnemus Linnaeus, 1758) as well as soil samples t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…For example, a significant positive correlation was found between metal concentrations in soil and the leaf and bark of T. aphylla in Tunisia [24]. The Magnisi peninsula at the Priolo Gargallo site shows a high degree of Pb and Hg contamination [19] and hosts sparse vegetation of Tamarix grown on a pyrite ash dump. Therefore, we speculate that the polluted soil on which Tamarix plants grow, coupled with the high bioaccumulation capacity of these plants, on whose sap O. heydeni feeds, affected the mtDNAcn of this species of insect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a significant positive correlation was found between metal concentrations in soil and the leaf and bark of T. aphylla in Tunisia [24]. The Magnisi peninsula at the Priolo Gargallo site shows a high degree of Pb and Hg contamination [19] and hosts sparse vegetation of Tamarix grown on a pyrite ash dump. Therefore, we speculate that the polluted soil on which Tamarix plants grow, coupled with the high bioaccumulation capacity of these plants, on whose sap O. heydeni feeds, affected the mtDNAcn of this species of insect.…”
Section: Discussionmentioning
confidence: 99%
“…The latter incorporates the natural harbor of Augusta and a large coastal marine area reaching as far as Syracuse, which extends 3 km offshore [16][17][18]. Within this perimeter, the Magnisi peninsula is heavily contaminated and is the site of a pyrite ash dump resulting from industrialization activities in the surrounding area [19]. Therefore, the peninsula was identified as the study area in this research.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of such classes of compounds have also for some time raised concerns about potential impacts on human and environmental health (Park et al, 2006;Weng et al, 2008;Cernigliaro et al, 2016Cernigliaro et al, , 2019Reinecke et al, 2016;Santoro et al, 2017;Yuan et al, 2018;Kafaei et al, 2019). In particular, topsoil from areas around oil refineries have been the subject of both chemical analyses (Li et al, 2009;Di Leonardo et al, 2014;Bayat et al, 2015;Benlaribi and Djebbar, 2020;Di Bella et al, 2020;Wang et al, 2020) and biological effects assessments using specific bioassay models which have provided evidence for multiple adverse effects (Höss et al, 2009;González et al, 2013;Hentati et al, 2013;Reinecke et al, 2016;Maisano et al, 2017;Copat et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In parallel with human health considerations, a range of studies have been carried out near petrochemical facilities on the analysis of environmental samples (see, e.g., Di Leonardo et al, 2014) soil-and sediment-based bioassays (Li et al, 2009;Höss et al, 2009;González et al, 2013;De Domenico et al, 2013;Signa et al, 2017;Caricato et al, 2019;Copat et al, 2020) which have clearly demonstrated the deleterious impact of these environmental samples, particularly those with high metal and polycyclic organic concentrations, on a number of biota, including marine organisms and human health (Mudu et al, 2014;Maisano et al, 2017;Gorini et al, 2020;Romano et al, 2021) as summarized in Table 1. However, a relevant task in evaluating the possibly adverse effects of soil in proximity of petrochemical facilities needed an ad hoc investigation.…”
Section: Introductionmentioning
confidence: 99%